Sustainability status, sensitive and key factors for increasing rice production: A case study in West Java, Indonesia - Rachman, Benny; Ariningsih, Ening; Sudaryanto, Tahlim; Ariani, Mewa; Septanti, Kartika Sari; Adawiyah, Cut Rabiatul; Ashari; Agustian, Adang; Saliem, Handewi Purwati; Tarigan, Herlina; Syahyuti; Yuniarti, Erny (PloS one, 2022)
The Indonesian rice production balance has managed to show a slightly consistent surplus recently, in the period of 2010 to 2021, but the country has continued to import rice to secure its rice reserve. The country has also made some efforts to increase its domestic rice production and, at the same time, faced ecological, socio-cultural, economic, institutional, and technological sustainability challenges. Previous studies on rice sustainability have shown varied results on the sustainability statuses and sensitive factors in Indonesia, yet there have been limited studies identifying key factors systematically. To provide more solid empirical evidence on this subject, a study to expand the scope to other sites with an additional analysis of the key factors is perceivably needed. This study aims to verify the sustainability status and identify sensitive factors as well as key factors for increasing rice production. The primary data were collected by interviewing officials from various agencies at the central and regional levels and several discussion groups of 40 participants, including farmers. In addition, secondary data were also collected from various ministries/agencies at the central and regional levels. Data analyses use a set of indicators, i.e., the Multidimensional Scaling (MDS) approach and the Matrix of Cross Impact Multiplications Applied to Classification (MICMAC) approach. The results show that the multidimensional sustainability status of increasing rice production in Bandung district is moderate, whereas sustainability status per dimension shows variations from poor to moderate. Fourteen out of 50 attributes are identified as sensitive factors influencing the sustainability of rice production. Six key factors are found to influence the sustainability of rice production. The study concludes that the sustainability status of increasing rice production in Bandung district is moderate, with variation across dimensions. The sustainability of increasing rice production in the study site is influenced by those 14 sensitive factors and those six key factors. This study recommends a number of major policies/programs to increase the sustainability of rice production, which are as follows: implementation of the Regional Spatial Plan, promotion of the application of best practices of farming management (organic fertilizers and pesticides), promotion of the use of agricultural machinery, and provision of farmer assistance for pre-harvest and postharvest production facilities, as well as farm financing. Future research should expand study sites to some other rice production centers with different attributes to enrich our understanding of the subject of rice sustainability.